Legal Politics toward Natural Energy: Natural Gas Utilization in Indonesia - Iqbal, Iqbal; Rayhannafi, Hilmi (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2023)
Indonesia is abundantly blessed with natural resources, including energy, among which natural gas holds a significant position. As of 2017, global demand for natural gas accounted for 23.4% of the total global primary energy demand. The substantial demand for natural gas can be attributed to its reputation as a clean and efficient energy source compared to fossil fuels. Natural gas possesses the potential to become a vital component of the energy mix, driving economic growth. Consequently, effective management of natural gas resources is essential to harness the full potential of oil and gas reserves in Indonesia, thereby maximizing benefits for the well-being of the population. In pursuit of this objective, the Indonesian government has implemented various regulations to provide a legal framework for natural gas management.